2006
DOI: 10.1152/ajpregu.00534.2004
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteins involved in potassium shifts during muscle activity and fatigue

Abstract: Kristensen, Michael, Thomas Hansen, and Carsten Juel. Membrane proteins involved in potassium shifts during muscle activity and fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 46 publications
1
62
0
Order By: Relevance
“…12-14) and on biochemical membrane fractionation studies in rat skeletal muscle (1). Indeed a compelling case for Kir channel localization on T-tubules and plasma membrane was made by Wallinga et al (15), who showed by modeling that maintenance of skeletal muscle excitability and excitation-contraction coupling during repetitive action potential firing requires the presence of Kir channels in these sites for clearance of K ϩ and prevention of positive shifts in the resting membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…12-14) and on biochemical membrane fractionation studies in rat skeletal muscle (1). Indeed a compelling case for Kir channel localization on T-tubules and plasma membrane was made by Wallinga et al (15), who showed by modeling that maintenance of skeletal muscle excitability and excitation-contraction coupling during repetitive action potential firing requires the presence of Kir channels in these sites for clearance of K ϩ and prevention of positive shifts in the resting membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…The large Na ϩ current at the sarcolemma enables fast conduction and increases the likelihood of initiating an AP in each t tubule, where the relatively small tubular Na ϩ current is normally adequate for propagation (253). Most of the resting K ϩ conductance is due to the K ϩ inward rectifier channels (Kir2.1), which are present at higher density in the T system than at the sarcolemma in mammalian muscle (249). The most common potassium channel on the sarcolemma is the ATP-sensitive K ϩ channel (K ATP or Kir6.2) (417); these channels are also found in the T system but at a lower density (331).…”
Section: Types and Distribution Of Ion Channelsmentioning
confidence: 99%
“…Expression of K ϩ -Cl Ϫ cotransporters KCC1, KCC3, and KCC4, as well as Na ϩ -K ϩ -Cl Ϫ cotransporter NKCC1, has been detected in skeletal muscle. [12][13][14][15][16][17] Interaction of K ϩ -Cl Ϫ cotransport with acid-base transport will be discussed later.…”
Section: Effects Of Acid-base Status On Internal K ؉ Distributionmentioning
confidence: 99%